2016
DOI: 10.1161/circulationaha.116.023686
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs in Cardiovascular Pathology, Diagnosis, and Therapy

Abstract: Vast parts of mammalian genomes encode for transcripts that are not further translated into proteins. The purpose of the majority of such noncoding ribonucleic acids (RNAs) remained paradoxical for a long time. However, a growing body of evidence demonstrates that long noncoding RNAs are dynamically expressed in different cell types, diseases, or developmental stages to execute a wide variety of regulatory roles at virtually every step of gene expression and translation. Indeed, long noncoding RNAs influence g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
126
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(128 citation statements)
references
References 112 publications
1
126
0
1
Order By: Relevance
“…LncRNAs were once considered to be the noise of genome transcription without biological function. However, recent studies have indicated that lncRNAs are closely related to many diseases, such as neurodegenerative diseases [32], cardiovascular diseases [33], rheumatoid diseases [34] and so on. Meanwhile, abnormal expressions of lncRNAs have been found in tumor tissues, which play important role in the carcinogenesis and aggressive progression of human malignancies [35].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs were once considered to be the noise of genome transcription without biological function. However, recent studies have indicated that lncRNAs are closely related to many diseases, such as neurodegenerative diseases [32], cardiovascular diseases [33], rheumatoid diseases [34] and so on. Meanwhile, abnormal expressions of lncRNAs have been found in tumor tissues, which play important role in the carcinogenesis and aggressive progression of human malignancies [35].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their variable origins, lncRNAs are ubiquitous and non‐nonsense sequences in the genome . LncRNAs have been found to play roles in cardiovascular diseases, neurodegenerative diseases, metabolism‐related disorders, bacterium infection, and diverse tumors . The aberrant expression of lncRNAs in various cancers has attracted attention, and the biological functions of lncRNAs are increasingly being shown.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Moreover, the level of MALAT1 was augmented in ischemic limbs 24 and higher in patients with MI than in healthy volunteers. [21][22][23] Moreover, the level of MALAT1 was augmented in ischemic limbs 24 and higher in patients with MI than in healthy volunteers.…”
Section: Discussionmentioning
confidence: 92%